Interações entre diferentes espécies de Candida na candidose experimental em modelos de invertebrados e vertebrados - Rossoni, Rodnei Dennis [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The aim of this study was to evaluate in vitro and in vivo interactions between different Candida species through the formation of biofilms in 96-well plates, induction of experimental candidiasis in Galleria mellonella model and immunosuppressed mice. We studied the standard strains of the following species: C. albicans (ATCC 18804), C. krusei (ATCC 6258) and C. glabrata (ATCC 90030). Monotypic biofilms of each species and heterotypic biofilms were performed on the bottom of 96-well plate for 48 h. Then, the amount of biofilm was analyzed by determining the number of colony forming units (CFU/mL). The larvae of G. mellonella were inoculated with homotypic and heterotypic suspensions of Candida (105 cells/mL) and incubated at 37°C. For 5 days, the number of dead larvae was assessed daily for survival curve analysis. In another experiment, after 0, 2, 4, 8, 12 and 24 h of infection with Candida, hemolymph of worms was extracted for counting the fungal cells (CFU/mL). For induction of oral candidiasis in mice, the animals were inoculated with homotypic or heterotypic microbial suspensions containing 108 cells/mL. After 48 h of the last inoculation, samples of the tongue were collected and seed in HiCrome chromogenic agar for counting of CFU/mL recovered from the oral cavity. Then, the animals were euthanized and their tongues removed for macroscopic and microscopic analysis. The analysis of Candida biofilms in vitro CFU/mL, the hemolymph of G. mellonella and recovery of mice were made by ANOVA, Tukey test or Student’s t test. The analysis of the survival curve was performed using GraphPad Prism using the Log-rank test (Mantel - Cox). Kruskal-Wallis or Mann-Whitney were applied for evaluation scores of macroscopic and histological analysis (p≤0,05). The results of biofilms in vitro have demonstrated a lower number of CFU/mL of C. albicans biofilms in heterotypic biofilm compared ...

O objetivo deste estudo foi avaliar in vitro e in vivo as interações entre as diferentes espécies de Candida por meio da formação de biofilme em placas de 96 poços, indução de candidose experimental em modelo de Galleria mellonella e de camundongos imunossuprimidos. Foram estudadas as cepas padrão das seguintes espécies: C. albicans (ATCC 18804), C. krusei (ATCC 6258) e C. glabrata (ATCC 90030). A partir de cada espécie, foram formados biofilmes monotípicos e heterotípicos no fundo da placa de 96 poços por 48 h. A seguir, a quantidade de biofilme formado foi analisada pela determinação do número de unidades formadoras de colônias (UFC/mL). G. mellonella foi inoculada com suspensões homotípicas e heterotípicas de Candida (105 células/mL) e incubadas a 37°C. Durante 5 dias, o número de lagartas mortas foi avaliado diariamente para análise da curva de sobrevivência. Em outro experimento, após 0, 2, 4, 8, 12 e 24 h da infecção por Candida, a hemolinfa das lagartas foi extraída para contagem das células fúngicas (UFC/mL). Para a indução da candidose bucal em camundongos, os animais foram inoculados com suspensões microbianas homotípicas ou heterotípicas contendo 108 células/mL. Após 48 h da última inoculação, amostras do dorso da língua foram coletadas e semeadas em ágar cromogênico HiCrome para contagem de UFC/mL recuperadas da cavidade bucal. Em seguida, os animais foram eutanasiados e as línguas retiradas para análise macroscópica e microscópica. A análise dos dados de UFC/mL dos biofilmes in vitro, de Candida na hemolinfa de G. mellonella e da recuperação dos camundongos foi feita por Análise de Variância, Teste de Tukey ou t de Student. A análise da curva de sobrevivência foi realizada utilizando o teste Log-rank (Mantel-Cox). Para avaliação dos escores obtidos na análise macroscópica e histológica foram aplicados os testes de Krusk-Wallis ou Mann-Whitney ...
Keywords: Candida; Candidiase; Patogenicidade; Modelos animais em pesquisa